2008
DOI: 10.1111/j.1398-9995.2007.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Original article: Evaluation of cytokine mRNA in induced sputum from patients with allergic rhinitis: relationship to airway hyperresponsiveness

Abstract: These findings suggest that VEGF and IL-5 can be important determinants of the development of AHR in AR patients and that lower levels of other cytokines may be associated with the absence of asthmatic symptoms in AR patients with AHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 35 publications
7
40
0
Order By: Relevance
“…A paper published by Ciprandi et al showed that FeNO values were higher in children with asthma and rhinitis in comparison with those suffering from rhinits alone, confirming that degree of airways inflammation depends on the involvement of both the nos and the lungs (28). Similar results were showed by Tufvesson et al even when evaluating cysteinyl-leukotrienes levels (29) and by Sohn et al when considering interleukin-5 and vascular endothelial growth factor levels (30). Finally, similar data were confirmed by Brown et al who, performing bronchial biopsies, showed increasing submucosal eosinophils and mast-cells levels (31).…”
Section: Allergic Rhinitis Isupporting
confidence: 75%
“…A paper published by Ciprandi et al showed that FeNO values were higher in children with asthma and rhinitis in comparison with those suffering from rhinits alone, confirming that degree of airways inflammation depends on the involvement of both the nos and the lungs (28). Similar results were showed by Tufvesson et al even when evaluating cysteinyl-leukotrienes levels (29) and by Sohn et al when considering interleukin-5 and vascular endothelial growth factor levels (30). Finally, similar data were confirmed by Brown et al who, performing bronchial biopsies, showed increasing submucosal eosinophils and mast-cells levels (31).…”
Section: Allergic Rhinitis Isupporting
confidence: 75%
“…Sputum eosinophil granule proteins have been extensively investigated in studies on allergic diseases as eosinophilic inflammatory markers commonly used for sputum (Ackerman et al 1983;Koh et al 2003;Badar et al 2004). In particular, studies have reported that the ECP was higher in the serum and sputum of asthma patients and AR patients (Sohn et al 2008;Hogan et al 2008). Both the ECP and EPO reflect the disease activity in AR, and a study reported that the ECP and EPO were predictors of the development of asthma in AR patients (Nielsen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Sputum induction and analysis were performed according to a standardized protocol (Sohn et al 2008). After the measurement of the basal FEV1, pretreatment was performed using 200 µg of salbutamol aerosol (Ventolin TM , GlaxoSmithKline, Bredtfred, England).…”
Section: Sputum Inductionmentioning
confidence: 99%
See 2 more Smart Citations